Layanan Pintar Perpustakaan Desa Dalam Meningkatkan Pendidikan Literasi Melalui User Education Dan Pembuatan Website Untuk Meningkatkan Akses Pemustaka Di Perpustakaan Desa Bekare Ponorogo - Khoirunnisak, Aliya; Yuki, Almaida Narita; Berliani, Azizma Lania; Wicaksani, Praheka Juang; Kurniawan, Neo Adhi (Universitas Pahlawan Tuanku Tambusai, 2024)
The village library is an effort by the village government and the community to increase interest in reading and literacy at the village level, and a means of information, education and culture centers. However, in its development, the performance of the village library has not achieved performance efficiency. Therefore, the implementation of this community service aims to increase interest in reading and provide information services to the village community through user education with observation, interview, and documentation collection techniques and coaching stages through the implementation of trials with the User Experience Questionnaire (UEQ) method. The results obtained from the implementation are that participants understand the meaning of the library, good behavior when reading books, and know the role of the village library as a source of information and knowledge and community satisfaction with the website that is easy to use because there are detailed website features. The next steps needed are librarian training and further website development.